2006
DOI: 10.1103/physrevlett.97.215503
|View full text |Cite
|
Sign up to set email alerts
|

Three-DimensionalGaNGa2O3Core Shell Structure Revealed by X-Ray Diffraction Microscopy

Abstract: In combination of direct phase retrieval of coherent x-ray diffraction patterns with a novel tomographic reconstruction algorithm, we, for the first time, carried out quantitative 3D imaging of a heat-treated GaN particle with each voxel corresponding to 17 x 17 x 17 nm3. We observed the platelet structure of GaN and the formation of small islands on the surface of the platelets, and successfully captured the internal GaN-Ga2O3 core shell structure in three dimensions. This work opens the door for nondestructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
79
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 129 publications
(79 citation statements)
references
References 24 publications
(16 reference statements)
0
79
0
Order By: Relevance
“…In our reconstructions, we terminated the algorithm after ∼150 iterations when the error function became stabilized. Both numerical simulations and experimental results from cryoelectron microscopy have indicated that EST produces superior results relative to FBP and the algebraic reconstruction technique when there is a limited number of projections as well as the missing wedge problem (12,39,40). After the 3D image was obtained by EST, we verified the fidelity of the reconstruction by calculating 25 diffraction patterns from the reconstructed 3D image.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…In our reconstructions, we terminated the algorithm after ∼150 iterations when the error function became stabilized. Both numerical simulations and experimental results from cryoelectron microscopy have indicated that EST produces superior results relative to FBP and the algebraic reconstruction technique when there is a limited number of projections as well as the missing wedge problem (12,39,40). After the 3D image was obtained by EST, we verified the fidelity of the reconstruction by calculating 25 diffraction patterns from the reconstructed 3D image.…”
mentioning
confidence: 86%
“…To address this problem, the EST method, an iterative reconstruction method that aims to solve for a portion of the missing projection data, was employed for the tomographic reconstruction. The EST method is coupled with an acquisition scheme for which the projections are acquired at equal slope intervals, instead of equal angle intervals, which results in the elimination of interpolative inaccuracies in conventional tomographic methods (12,39,40). EST iterates back and forth between real and reciprocal space.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…'. Indeed, since Sayre's first proposal of the method (Sayre, 1980) and its first demonstration by Miao (1999), it has been used to image three-dimensional micro-fabricated structures (Chapman, Barty, Beetz et al, 2006), small biological cells (Miao et al, 2003;Shapiro et al, 2005;Thibault et al, 2006), metallic microcrystals (Robinson et al, 2001;Pfeifer et al, 2006), ultralow-density foams (Barty et al, 2007) and quantum dots, among others (Miao et al, 2006). The maturity of the field can be most clearly seen in two recent contributions from Chapman and Barty.…”
mentioning
confidence: 99%
“…The program suite contains many useful tools for image analysis that could be used for analyzing XFEL data. We tested our reconstruction program using experimental diffraction data of an aerosol nanoparticle obtained by tomographic coherent X-ray diffraction microscopy (CXDM) (Miao et al, 2006;Barty et al, 2008;Jiang et al, 2010) instead of data from XFEL. These data are very similar to those from XFEL experiments, the main difference being that XFEL is 'single-shot' while X-ray diffraction microscopy allows (weaker but) repeating exposure.…”
Section: Introductionmentioning
confidence: 99%